2021
DOI: 10.1007/s00112-021-01159-z
|View full text |Cite
|
Sign up to set email alerts
|

Die induzierbare laryngeale Obstruktion (ILO) – Ursachen, klinische Präsentation, Diagnostik und Therapie

Abstract: ZusammenfassungWiederholt episodenhaft auftretende Atemnot ist im Kindes- und Jugendalter ein häufiges Symptom. Neben anstrengungsinduzierter Bronchialobstruktion im Rahmen eines Asthma bronchiale ist eine funktionelle Genese eine sehr häufige Differenzialdiagnose. Dennoch wird diese Diagnose häufig nicht oder mit langer Latenz gestellt. Unter dem Oberbegriff „ILO“ („inducible laryngeal obstruction“) werden sowohl funktionelle supraglottische Obstruktionen durch Kollaps der Knorpelstrukturen als auch Dysfunkti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The data reported here are in concordance with the published literature and support the evidence that long-term sequelae after SARS-CoV-2 infection in children are rare. Some authors have suggested a possible link to dysfunctional breathing (for example inducible laryngeal obstruction) after SARS-CoV-2 infection (36), a condition that is well known to occur after other (infectious) triggers (53). Further studies are needed to elucidate this possible pathological link.…”
Section: Discussionmentioning
confidence: 99%
“…The data reported here are in concordance with the published literature and support the evidence that long-term sequelae after SARS-CoV-2 infection in children are rare. Some authors have suggested a possible link to dysfunctional breathing (for example inducible laryngeal obstruction) after SARS-CoV-2 infection (36), a condition that is well known to occur after other (infectious) triggers (53). Further studies are needed to elucidate this possible pathological link.…”
Section: Discussionmentioning
confidence: 99%